(untitled) (Elmergib Journal of Human Sciences, 2025)
The acquisition and learning of language represent one of humanity’s most complex cognitive achievements, sparking diverse theoretical perspectives among researchers. This paper explores the foundational and evolving viewpoints on how individuals master language, moving beyond the traditional "nature versus nurture" dichotomy. It begins by examining Noam Chomsky’s nativist theory, highlighting his crucial distinction between linguistic competence (innate knowledge) and performance (actual language use), and the concepts of Universal Grammar and the Language Acquisition Device. While Chomsky’s work profoundly influenced linguistics, psychology maintained a strong interest in observable language performance. The paper then delves into B.F. Skinner’s behaviorist account, which posits language as learned through reinforcement. Subsequently, it discusses cognitive theories, including Jean Piaget’s emphasis on language emerging from general intellectual development, and Lev Vygotsky’s sociocultural perspective, which stresses the role of social interaction and cultural tools. Critiques of these early theories, such as the challenges posed by specific genetic disorders, are also addressed. Finally, the paper explores modern, integrative approaches like functional linguistics, usage-based theories, connectionism, and emergentism, which seek to synthesize insights from various disciplines, emphasizing dynamic interactions between innate predispositions, environmental input, and general cognitive learning mechanisms. This comprehensive review underscores that language acquisition is a multifaceted phenomenon requiring an interdisciplinary understanding